A single bout of moderate-intensity aerobic exercise improves motor learning in premanifest and early Huntington’s disease - Andrews, Sophie C.; Kämpf, Lydia; Curtin, Dylan; Hinder, Mark; Wenderoth, Nicole; Stout, Julie C.; Coxon, James P. (Frontiers in Psychology, 2023)
Introduction Cardiorespiratory exercise has emerged as a promising candidate to modify disease progression in Huntington’s disease (HD). In animal models, exercise has been found to alter biomarkers of neuroplasticity and delay evidence of disease, and some interventions–including exercise–have shown benefits in human HD patients. In healthy human populations, increasing evidence suggests that even a single bout of exercise can improve motor learning. In this pilot study, we investigated the effect of a single bout of moderate intensity aerobic exercise on motor skill learning in presymptomatic and early manifest HD patients. Methods Participants were allocated to either an exercise (n = 10) or control (n = 10) group. They performed either 20 min of moderate intensity cycling or rest before practicing a novel motor task, the sequential visual isometric pinch force task (SVIPT). After 1 week, the retention of the SVIPT was measured in both groups. Results We found that the exercise group performed significantly better during initial task acquisition. There were no significant differences in offline memory consolidation between groups, but total skill gain across both acquisition and retention sessions was greater in the group who exercised. The better performance of the exercise group was driven by improvements in accuracy, rather than speed. Discussion We have shown that a single bout of moderate intensity aerobic exercise can facilitate motor skill learning in people with HD gene-expansion. More research is needed to investigate the underlying neural mechanisms and to further explore the potential for neurocognitive and functional benefits of exercise for people with HD.